2014
DOI: 10.1007/s10640-014-9809-5
|View full text |Cite
|
Sign up to set email alerts
|

Consumption-Based Adjustment of Emissions-Intensity Targets: An Economic Analysis for China’s Provinces

Abstract: China's Twelfth Five-Year Plan (2011-2015 aims to achieve a national carbon intensity reduction of 17 % through differentiated targets at the provincial level. Allocating the national target among China's provinces is complicated by the fact that more than half of China's national carbon emissions are embodied in interprovincial trade, with the relatively developed eastern provinces relying on the center and west for energy-intensive imports. This study develops a consistent methodology to adjust regional emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…8 From a political perspective, adopting allocation schemes which generate large interregional transfers could be challenging. An analysis of the regional emissions-intensity targets of the China's Twelfth Five-Year Plan has shown that the eastern provinces currently shoulder a relatively modest reduction burden compared to that of the central and western provinces (see Supplementary Section S11 and Springmann et al 2015). The potentially negative consequences for the eastern provinces in those scenarios that are preferred by most survey participants may hinder adoption given the political and economic influence that those provinces have.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 From a political perspective, adopting allocation schemes which generate large interregional transfers could be challenging. An analysis of the regional emissions-intensity targets of the China's Twelfth Five-Year Plan has shown that the eastern provinces currently shoulder a relatively modest reduction burden compared to that of the central and western provinces (see Supplementary Section S11 and Springmann et al 2015). The potentially negative consequences for the eastern provinces in those scenarios that are preferred by most survey participants may hinder adoption given the political and economic influence that those provinces have.…”
Section: Resultsmentioning
confidence: 99%
“…We consider two criteria based on emissions intensity, the environmental reward and environmental subsidy criteria (see, e.g., Eyckmans and Finus 2004), due to China's focus on emissions intensity as a policy target. We also add a consumer-pays criterion to account for the significant regional separation that exists within China between production and consumption activities and their associated CO 2 emissions (Meng et al 2011;Guo et al 2012;Feng et al 2013;Springmann et al 2015).…”
Section: Permit Allocation and Equity Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The foregoing models have principally been used to analyze the macroeconomic consequences of emission reduction policies at multiple scales-traditionally international, 13 but increasingly regional and national, 14 and even subnational Springmann et al, 2014) or sectoral (Rausch and Mowers, 2014). CGE models' key advantage is their ability to quantify complex interactions between climate policies and a panoply of other policy in-struments and characteristics of the economy.…”
Section: Ghg Omentioning
confidence: 99%
“…Markandya et al [24] used the CGE model to analyze and compare the differences between developing countries and developed countries in a trade-off between traditional economic development and low-carbon development and found that the adverse impact of the implementation of emissions reduction policies on developing countries is huge. Springmann et al [25] explored the distribution of carbon quotas among different provinces in China. The results show that eastern China outsourced 14% of its own carbon quotas to central and western regions.…”
Section: Introductionmentioning
confidence: 99%